Türkiye'de Turizmin ve Finansal Gelişmenin Ekonomik Büyümeye Katkısı: Turizme Dayalı Büyüme Hipotezi Analizi - Yurtkuran, Süleyman (Muş Alparslan Üniversitesi, 2020)
This study empirically investigated the impact of tourism and financial development on the real gross domestic product (GDP) of Turkey by using autoregressive-distributed lag (ARDL) bounds test, fully modified ordinary least squares (FMOLS), dynamic ordinary least squares (DOLS) and canonical cointegrating regression (CCR) long-run estimators and vector error correction model (VECM) during the period of 1964-2017. The result of a cointegration test found that there was a long-run relationship between these series. The long-term coefficients obtained from the ARDL, FMOLS, DOLS and CCR showed that increase in tourism revenue and financial development lead to economic growth. The outcomes of VECM indicated a long run unidirectional causality running from tourism revenue and financial development to economic growth and short run unidirectional causality running from financial development to economic growth.

Bu çalışmada Türkiye’de 1964-2017 döneminde turizmin ve finansal gelişmenin gayri safi yurt içi hasıla (GSYİH) üzerindeki etkisi; gecikmesi dağıtılmış otoregresif model (ARDL) sınır testi, tam değiştirilmiş en küçük kareler (FMOLS), dinamik en küçük kareler (DOLS) ve kanonik eşbütünleşme regresyonu (CCR) uzun dönem tahmincileri ve vektör hata düzeltme modeli (VECM) yardımıyla araştırılmıştır. Eşbütünleşme testi sonucuna göre seriler arasında uzun dönemde eşbütünleşme ilişkisi olduğu bulunmuştur. ARDL, FMOLS, DOLS ve CCR tahmincilerinden elde edilen katsayılara göre uzun dönemde turizm gelirlerindeki artış ile finansal gelişmenin ekonomik büyümeyi arttırdığı sonucuna ulaşılmıştır. VECM’den elde edilen sonuçlara göre kısa dönemde finansal gelişmeden ekonomik büyümeye doğru tek yönlü, uzun dönemde ise turizm gelirlerinden ve finansal gelişmeden ekonomik büyüme doğru tek yönlü bir nedensellik ilişkisi olduğu belirlenmiştir.
The Contribution of Tourism and Financial Development to Economic Growth in Turkey: An Analysis of Tourism-Led-Growth Hypothesis
anemon
Keywords: Tourism Led Growth Hypothesis; Economic Growth; Tourism Revenue; Turkey; Turizm’e Dayalı Büyüme Hipotezi; Ekonomik Büyüme; Turizm Gelirleri; Türkiye